Loading of a porous rock with constant micro-seismic event rate suppresses seismicity and promotes subcritical failure - Maria-Daphne Mangriotis; Alexis Cartwright-Taylor; Ian G. Main; Andrew Curtis; Andrew F. Bell; Ian B. Butler; Florian Fusseis (Scientific Reports)
Abstract Catastrophic failure is the end result of progressive localisation of damage creating brittle failure on a variety of system scales in the Earth. However, the factors controlling this evolution, and the relationship between deformation and the resulting earthquake hazard, are not well constrained. Here we address the question of how to adapt operational controls in a strain-inducing laboratory experiment so as to minimize associated microseismicity. We simultaneously image the induced damage using x-rays at a synchrotron, and detect acoustic emissions which can be fed back to change operational controls on the experiment. We confirm that using continuous servo-control based on acoustic emission event rate not only slows down deformation compared to standard constant strain rate loading, but also suppresses events of all sizes, including extreme events. We develop a new model that explains this observation, based on the observed evolution of microstructural damage and the fracture mechanics of subcritical crack growth. The model is independently consistent with the observed stress history and acoustic emission statistics. Our results imply that including seismic event rate control may improve risk management of induced seismicity over a range of event magnitudes, if similar processes are relevant at larger scales.